2011
DOI: 10.1111/j.1948-7134.2011.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various configurations of CDC-type traps for the collection of Phlebotomus papatasi Scopoli in southern Israel

Abstract: We conducted two experiments to determine the best CDC-trap configuration for catching male and female Phlebotomus papatasi. First, visual features were evaluated. Standard CDC traps were modified to have black or white catch bags, black or white lids, or no lids and these were tried in different combinations. Significantly more male sand flies were caught by darker traps; significantly more females were captured by traps with either all black or a combination of black and white features. Attraction may be due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Our findings are consistent with Haddad et al () where this species was captured inside houses and barns. It was demonstrated that P. papatasi resting sites depend on vegetation cover, type of vegetation, and the presence of a mulch layer, and were absent in bare soil and little shade (Müller et al ). Also, this fly prefers disturbed habitats as resting sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with Haddad et al () where this species was captured inside houses and barns. It was demonstrated that P. papatasi resting sites depend on vegetation cover, type of vegetation, and the presence of a mulch layer, and were absent in bare soil and little shade (Müller et al ). Also, this fly prefers disturbed habitats as resting sites.…”
Section: Discussionmentioning
confidence: 99%
“…The sand flies of Palestine were studied from the Jordan Valley (Müller et al and ), Jerusalem Mountains (Orshan et al , Moncaz et al ), the north (Svobodova et al ), and Jenin area (Sawalha et al , Depaquit and Léger, ). Regionally, the sand flies of neighboring countries were identified in Egypt (Lane ), Jordan (Lane et al , Kamhawi et al , Kanani et al ), Lebanon (Haddad et al ), and Saudi Arabia (Lewis and Buttiker ).…”
Section: Introductionmentioning
confidence: 99%
“…The REDILA trap is made with cheap materials, mostly available at field localities, and is easy to build and repair with minimal skills, so as to avoid the need for excessive traps for sand fly monitoring. We compared the REDILA black and white light traps, as there are reports that Nyssomyia whitmani prefers black light Shannon traps while Migonemyia migonei prefers white light (Galati et al Moschin et al In addition, the black or UV lights are usually more productive, mainly with anthropophilic species (Kline et al Hashiguchi et al Müller et al Trap performance was compared in different environmental settings in relation to presence/absence and abundance of Lutzomyia longipalpis, Mg. migonei , and Ny. whitmani , some of the most important vectors of Leishmania infantum and Leishmania braziliensis in Argentina (Quintana et al Therefore, the aim of this study was to determine whether the REDILA trap, with feasible and affordable characteristics, could be used as an alternative to CDC light traps for surveillance of phlebotomine sand flies.…”
Section: Introductionmentioning
confidence: 99%
“…CO2 is usually a long-range attractant for sandflies whereas light is probably perceived by sandflies at much closer range [24]. The addition of a source of CO2 can therefore improve catches by increasing the effective sampling area of a light trap [25,26]). The productivity of a light trap or CO2 baited-trap depends on several factors such as: the position; type of light used; species of sandflies to be collected; physiological conditions of sandfly adults; environmental conditions during the collection; the amount of contrast between the light source and surroundings: the greater the contrast, the greater the 'catchment area'; sandflies have a tendency to withdraw from the high light intensity immediately adjacent to lamp.…”
Section: Light Traps and Co2 Trapsmentioning
confidence: 99%